1
$\begingroup$

The full question is:
If $m$, then $h$.
We have either $h$ or $w$.
Therefore, if not $h$, then I will not have $m$ and I have $w$.
Show that this above argument is logically valid.

Let $h,w,m$ be propositions. Argument 1 is
$$\begin{align}&m\rightarrow h \\ &h\vee w \end{align}$$ $$ \rule{2in}{.5pt}$$ $$\therefore\neg h \rightarrow (\neg m)\wedge w$$

Argument 2 is
$$\begin{align}&m\rightarrow h\\ &h\vee w \\ &\neg h \end{align}$$ $$\rule{2in}{.5pt}$$$$\therefore (\neg m)\wedge w$$

Are these saying the same thing? I'm trying to be 100% correct about this. The first two compound propositions were premises, and the question said
"If not $h$, then I will not have $m$ and I have $w$".

So I'm not sure if I can say $\neg h$ is a premise (or assumption) from question, and this leads to $(\neg m) \wedge w$, meaning $\neg h \rightarrow (\neg m)\wedge w$ (this is for argument 2)

The solution says argument 1 is the solution.

$\endgroup$
1
$\begingroup$

\begin{align} \text{Given: }\qquad m &\rightarrow h \\ \therefore\quad \lnot\, h &\rightarrow \lnot\, m \\ \\ \text{Given: }\qquad h &\vee w \\ \therefore\quad \lnot\, h &\rightarrow w \\ \\ \text{taken together: }\quad\lnot\, h &\rightarrow \lnot\, m \land w \\ \end{align}

$\lnot\, h$ is not an outcome; the implications of $\lnot\, h$ are the outcome. However if you are given $\lnot\, h$ as a premise, you can then detach the implication from the statement and give those as an outcome. so:

\begin{align} \text{Given: }\quad\lnot\, h &\rightarrow \lnot\, m \land w \\ \text{and: }\qquad\lnot\, h \\ \therefore\quad \lnot\, m &\land w \\ \end{align}

$\endgroup$
  • $\begingroup$ So argument 2 is the 100% correct one then? (we shouldn't ever have implication arrows in the conclusion/outcome?) $\endgroup$ – Natash1 Sep 16 '17 at 6:13
  • $\begingroup$ Added the argument through to matching your argument 2 also $\endgroup$ – Joffan Sep 16 '17 at 6:21
2
$\begingroup$

Rather, I'd say your "argument 2" is the step before proving "argument 1".

You take the premises $\bbox[lemonchiffon]{m\to h}$ and $\bbox[lemonchiffon]{h\vee w}$, and make assumption $\bbox[lemonchiffon]{\neg h}$ to conclude $\bbox[lemonchiffon]{\neg m\wedge w}$, then you discharge the assumption to demonstrate what was to be proven: that if the premises are justified then, $\bbox[lemonchiffon]{\neg h\to (\neg m\vee w)}$.


Since $\bbox[lemonchiffon]{{m\to h, \neg h\vdash \neg m}}$ (by modus tollens) and $\bbox[lemonchiffon]{{h\vee w, \neg h\vdash w}}$ (by disjunctive syllogism), therefore $ \bbox[lemonchiffon]{m\to h, h\vee w, \neg h~\vdash ~\neg m\wedge w}$ (by conjunctive introduction).   Since that, therefore $\bbox[lemonchiffon]{ m\to h, h\vee w~\vdash ~\neg h\to (\neg m\wedge w)}$ (by conditional introduction).   Thus demonstrating that the argument is valid.

$$\dfrac{m\to h\\ h\vee w}{\neg h\to (\neg m\wedge w)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.